Molecular and Metabolic Reprogramming: Pulling the Strings Toward Tumor Metastasis - Hipólito, Ana; Martins, Filipa; Mendes, Cindy; Lopes-Coelho, Filipa; Serpa, Jacinta (Frontiers in Oncology, 2021)
Metastasis is a major hurdle to the efficient treatment of cancer, accounting for the great majority of cancer-related deaths. Although several studies have disclosed the detailed mechanisms underlying primary tumor formation, the emergence of metastatic disease remains poorly understood. This multistep process encompasses the dissemination of cancer cells to distant organs, followed by their adaptation to foreign microenvironments and establishment in secondary tumors. During the last decades, it was discovered that these events may be favored by particular metabolic patterns, which are dependent on reprogrammed signaling pathways in cancer cells while they acquire metastatic traits. In this review, we present current knowledge of molecular mechanisms that coordinate the crosstalk between metastatic signaling and cellular metabolism. The recent findings involving the contribution of crucial metabolic pathways involved in the bioenergetics and biosynthesis control in metastatic cells are summarized. Finally, we highlight new promising metabolism-based therapeutic strategies as a putative way of impairing metastasis.